Capital structure moderation on the effect of net profit margin on company value in the manufacturing company sector for the 2015-2019 period - Nurlelah, Nurlelah; Suheti, Suheti; Sumarni, Meli; Haryadi, Didit (Trigin Publisher, 2024)
This study investigates the interaction between capital structure, net profit margin, and company value in the manufacturing sector in Indonesia. The goal is to gain insight into how these factors interact and affect the overall value of a company in a particular region and industry. This analysis uses quantitative methods based on financial data and relevant metrics for a sample of 30 manufacturing companies operating in Indonesia. This study examines the relationship between capital structure, net profit margin, and company value through statistical analysis and linear regression modeling techniques with SPSS version 26. The results showed that capital structure net profit margin significantly affected the company's value in the manufacturing industry. The capital structure reinforces the effect of the net profit margin on the company's value. The findings contribute to the existing literature on company valuations by providing empirical evidence specific to the manufacturing sector in West Java. The research has implications for policymakers, investors, and managers, as it offers valuable insights into the factors that drive corporate value in the industry, helping stakeholders make decisions and strategies to improve performance and competitiveness. Provide benefits in the context of financial management.